Peran Mahasiswa KKN dalam Bimbingan Belajar dan Mengaji untuk Generasi Emas di Nagari Tanjuang Bungo - Najmi; Viora Agustin; Melinda Saputri; Sabrina Aufa; Fadhil Naufal Azmi; Ikromil Hakim (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The Community Service Program (KKN) is a concrete form of student involvement in community service, implemented as part of the Tri Dharma of Higher Education. This program aims to benefit the community and the surrounding environment. This article discusses the role of KKN students in organizing tutoring and Quranic recitation activities in Nagari Tanjuang Bungo as a contribution to achieving quality education for the younger generation. Students act as facilitators, helping to improve literacy and understanding of religious values in children. This activity aligns with SDGs 4, which aims to support the improvement of quality education. This tutoring activity has shown increased motivation to learn and Quranic reading skills in children. It also creates a learning environment that supports the growth of a knowledgeable, intelligent, and competitive golden generation.